P03.09.A Proton beam therapy for adults medullobastoma. (5th September 2022) - Frakulli, R; Ni, N; Schmidt, L; Guntrum, F; Kramer, P; Frisch, S; Glas, M; Timmermann, B
Abstract: Background: Although Medulloblastoma (MB) is the most common primary malignant intracranial tumor in childhood, in adults it is extremely rare. Therefore, available data is scarce and experience with radiation and proton beam therapy (PBT) is very limited. The treatment typically includes tumour resection, irradiation of the craniospinal axis (CSI) followed by a boost, +/- concomitant chemotherapy, and maintenance therapy. Herein, we present our preliminary analysis of outcome and toxicity after PBT. Material and Methods: Patients ≥ 18 years with primary MB treated with PBT between January 2017 and March 2020 enrolled in the prospective registry study (DRKS00004384) were evaluated in this analysis. Within the registry, adverse events were documented according to CTCAE v4.0 before, during, and after PT. The overall survival (OS), local control (LC) and higher-grade toxicity (≥ grade 3) were analyzed. Results: A total of 19 patients (13 males, 6 females) with a median age of 23 years (range, 18.5- 39 years) were included in this study. Histopathology type were classic, desmoplastic /extensive nodularity or anaplastic MB in 52.6%, 26.3% and 21.1 % of patients, respectively. Complete tumor resection was performed in 57.8 % of patients. 68.4 % of patients had local disease without any metastases. Median total CSI dose was 35.2 Gy(RBE) (range, 23.4-40 Gy) with a median single dose of 1.6 Gy(RBE) (range, 1-1.8 Gy). All patients received either boost to the posterior fossa (57.9%) or to the tumor bed only (42.1%). The median total tumor dose was 18.8 Gy(RBE) (range, 54-68 Gy). Concomitant chemotherapy was given to 63.1% of patients. The median follow-up time after first diagnosis was 28.2 months (range, 8-56 months). No higher-grade acute or late adverse event was documented so far. One patient developed local disease progression. Another patient deceased due to an acute pulmonary embolism during maintenance chemotherapy without evidence of disease. The 3-year LC and OS rate were 89 % and 94 %, respectively. Conclusion: Early results display good feasibility and high tumor control of PT in adult patient with MB. Results will need to be confirmed in larger cohort with longer follow-up time.